Simulating the Dynamics of Early Marriage and Marital Stability Using SERH Mathematical Models - Khairana, Nadiyah; Annas, Suwardi; Side, Syafruddin; Sainon Andi Pandjajangi, Andi Muhammad Ridho Yusuf (Jurnal Varian, 2025)
This study aims to develop a mathematical model of SERH (Susceptible, Engaged, Risk, and Stabilization) to analyze and predict the incidence of early marriage in South Sulawesi Province. The research employs method a combination of theoretical and applied approaches, utilizing differential equations to model the dynamics of early marriage spread. Data were collected through questionnaires distributed to 400 couples selected using the Slovin technique, representing a population of 57,789 couples. The SERH model parameters, including the rate of couple interaction , transition from engagement to risk , and recovery from risk to stability , were derived from the collected data. Simulations were conducted using Maple software to visualize the spread of early marriage under different scenarios. The results of the analysis revealed two equilibrium points: a marriage-free equilibrium and a stable endemic equilibrium. The basic reproduction number  was calculated to be 3.97, indicating that one couple can influence 3-4 others in their social environment. However, with effective interventions such as education and counseling, the R₀ value can be reduced to 0.45, significantly lowering the spread of early marriage. This study provides valuable insights for policymakers to design targeted prevention programs and highlights the importance of early intervention in reducing the prevalence of early marriage.